Practical Synthesis of Polyamine Succinamides and Branched Polyamines. Issue 10 (25th October 2022) - Alkhzem, Abdulaziz H.; Laabei, Maisem; Woodman, Timothy J.; Blagbrough, Ian S.
Abstract: Antibiotic resistance is now a growing threat to human health, further exacerbated by the lack of new antibiotics. We describe the practical synthesis of a series of substituted polyamine succinamides and branched polyamines that are potential new antibiotics against both Gram‐positive and Gram‐negative bacteria, including MRSA and Pseudomonas aeruginosa . They are prepared via 1, 4‐Michael addition of acrylonitrile and then hydrogenation of the nitrile functional groups to primary amines. They are built upon the framework of the naturally occurring polyamines thermine (3.3.3, norspermine) and spermine (3.4.3), homo‐ and heterodimeric polyamine succinic amides. Linking two of the same or different polyamines together via amide bonds can be achieved by introducing a carboxylic acid group on the first polyamine, then coupling that released carboxylic acid to a free primary amine in the second polyamine. If the addition of positive charges on the amino groups along the polyamine chains are a key factor in their antimicrobial activity against Gram‐negative bacteria, then increasing them will increase the antimicrobial activity. Synthesising polyamine amide dimers will increase the total net positive charge compared to their monomers. The design and practical synthesis of such homo‐ and hetero‐dimers of linear polyamines, spermine and norspermine, are reported. Several of these compounds do not display significant antibacterial activity against Gram‐positive or Gram‐negative bacteria, including MRSA and Pseudomonas aeruginosa . However, the most charged analogue, a branched polyamine carrying eight positive charges at physiological pH, displays antibiofilm activity with a 50 % reduction in PAO1 at 16–32 μg mL −1 . Abstract : Building upon the framework of naturally occurring polyamines, the practical synthesis of a series of substituted homo‐ and hetero‐dimers of linear polyamines, spermine and norspermine succinamides and branched polyamines is achieved via 1, 4‐Michael addition of acrylonitrile and then hydrogenation of the nitrile functional groups to primary amines. The most charged analogue, a branched polyamine carrying eight positive charges at physiological pH, displays antibiofilm activity with a 50 % reduction in PAO1 at 16–32 μg mL −1 .